Optimal frequency of individualised nutrition counselling in patients with head and neck cancer receiving radiotherapy: A systematic review. Issue 1 (18th June 2021) - Tunzi, Liana; Funk, Tessa; Brown, Teresa; Findlay, Merran; Bauer, Judith
Abstract: Background: Head and neck cancers (HNC) are strongly associated with malnutrition. This systematic review aimed to investigate the optimal frequency of individualised nutrition counselling (INC) pre‐, peri‐ and post‐treatment for patients with HNC. Methods: Pubmed, EMBASE, Cinahl and Scopus were searched from inception through to April 2020 to identify randomised controlled trials (RCTs) that focused on the INC frequency for adult patients with HNC (Registration no. 178868). The outcomes assessed were nutritional status, dietary intake, weight change, treatment interruptions, unplanned hospital admissions, quality of life, complications and morbidity. Certainty of evidence was assessed using Grades of Recommendation, Assessment, Development and Evaluation (GRADE). Results: Four RCTs were identified with five papers ( n  = 500 total participants). The certainty of evidence was 'high' for nutritional status and quality of life, 'moderate' for treatment interruptions and unplanned hospital admissions, and 'low' for percentage weight change, complications/morbidity and dietary intake. Compared to control groups, there were consistent improvements for nutritional status, quality of life, treatment interruptions, unplanned hospital admissions, dietary intake, percentage weight change and morbidity when weekly INC was provided peri‐treatment and fortnightly INC was provided post‐treatment. No statistical significance was found for treatment interruptions, dietary intake and weight change when INC was provided fortnightly peri‐treatment only. There were no RCTs in the current review that offered INC pre‐treatment. Conclusions: This systematic review shows beneficial effects with weekly INC peri‐treatment and fortnightly INC post‐treatment for patients with HNC in all outcomes studied. Future research should focus on models of care to address the optimal frequency of pre‐treatment INC as well as the duration of post‐treatment INC.